2014
DOI: 10.1016/j.aap.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enforcement intensity on alcohol impaired driving crashes

Abstract: Background Research measuring levels of enforcement has investigated whether increases in police activities (e.g., checkpoints, driving-while-intoxicated [DWI] special patrols) above some baseline level are associated with reduced crashes and fatalities. Little research, however, has attempted to quantitatively measure enforcement efforts and relate different enforcement levels to specific levels of the prevalence of alcohol-impaired driving. Objective The objective of this study was to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…For example, Fell et al (2014) concluded from the data of the US National Roadside Survey that a 10% increase in the DUI arrest rate is associated with a 1% reduction in the drinking driver crash rate. In their meta-analysis on the effect on crashes of DUI checkpoints, Erke et al (2009) found that crashes involving alcohol are reduced by minimum 17% and that all crashes, independently of alcohol involvement, are reduced by about 10-15%.…”
Section: Alcohol Checksmentioning
confidence: 97%
“…For example, Fell et al (2014) concluded from the data of the US National Roadside Survey that a 10% increase in the DUI arrest rate is associated with a 1% reduction in the drinking driver crash rate. In their meta-analysis on the effect on crashes of DUI checkpoints, Erke et al (2009) found that crashes involving alcohol are reduced by minimum 17% and that all crashes, independently of alcohol involvement, are reduced by about 10-15%.…”
Section: Alcohol Checksmentioning
confidence: 97%
“…It is in local communities that these laws are enforced and reductions in alcohol-related traffic crashes save lives. Agencies have been using many strategies to enforce these laws, such as sobriety checkpoints, HVE, specialized DWI units, and most recently no refusal blood draw search warrant operations (Dula, Dwyer, and LeVerne 2007;Fell, Tippetts, and Levy 2008;Fell et al 2014;Wiliszowski and Jones 2003;Williams 2006). Enforcement of these particular laws comes at a cost, and must compete against other police responsibilities.…”
Section: Introductionmentioning
confidence: 98%
“…In 2012, this number reduced to 21 percent. Although this progress has been cited as remarkable and substantial, alcoholrelated traffic crashes still accounted for 10,322 fatalities in 2012 (Shults et al 2001;NHTSA 2012;Fell et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a nationally representative study, Fell et al [3] found that a 10% increase in the DWI arrest rate per capita in a community was associated with a 1% decrease in alcohol-impaired driving crashes in that locality. Using a 11-year sample (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of state data from the Fatality Analysis Reporting System, Yao et al…”
Section: Relationship Of Arrests To Impaired Driving Crashesmentioning
confidence: 99%
“…In a nationally representative study, Fell et al [3] found that a 10% increase in the DWI arrest rate per capita in a community was associated with a 1% decrease in alcohol-impaired driving crashes in that locality. Using a 11-year sample (1996-2006) of state data from the Fatality Analysis Reporting System, Yao et al [4]-in a paper in this issue-studied states with increases and decreases in the percentage of alcohol-impaired fatal crashes during that 11-year period and found that states that had higher DWI arrest rates per capita had reductions in the percentage of fatal crashes involving an alcohol-impaired driver.…”
Section: Relationship Of Arrests To Impaired Driving Crashesmentioning
confidence: 99%